Metrics on surgical topics in Revista Información Científica, 2018-2022 - Yanier Espinosa Goire; José Manuel Padilla González; Andy Guillermo Paumier Durán; Héctor Manuel Verdecia Rodríguez; Luis Manuel Abreu Pereira (Revista Información Científica)
Introduction: research on surgical topics is essential to advance the comprehensive care of the sick patient. Updated scientific production published systematically influences the course of research practice.